Kajian Kerentanan Keamanan Website Universitas XYZ Menggunakan Framework Open Web Application Security Project (OWAS) - Ramadhan, Teguh Reskya; Amelia, Riska; Sunaryo, Budi; Zulfadli, Zulfadli; Arnita, Arnita (Ikatan Ahli Informatika Indonesia, 2024)
Website security is a critical priority for educational institutions, including XYZ University, to safeguard their data and services from cyber threats. This study aims to assess the security vulnerabilities of XYZ University's website using the Open Web Application Security Project (OWASP) framework. The analysis revealed that the website has high-security risks with multiple vulnerabilities, such as Injection, Cross-Site Scripting (XSS), and Security Misconfiguration. The study employs an OWASP-based approach, encompassing risk identification, vulnerability analysis, and mitigation recommendations. The findings indicate that the primary weaknesses stem from inadequate input data protection, delayed software updates, and weak access controls. This research provides strategic recommendations to mitigate security risks, including strengthening input validation, updating systems, and implementing robust data encryption mechanisms. The results are expected to enhance the security posture of XYZ University's website and serve as a reference for proactive measures against cyber threats.